Bibliometric Analysis Of Publications Related To Surah Al-Nahl: Towards Research In I’Jaz Studies - Aisyah Humairaa Muhammad Faisal; Maryam Mokhtar; Tg. Ainul Farha Binti Abdul Rahman; Faszly Rahim (Universiti Sains Islam Malaysia, 2024)
Proceedings of the 7th International Prophetic Conference (SWAN) 2020 FPQS,Universiti Sains Islam Malaysia, 29-30 October 2020 Paper No. BI008 77-89